2015
DOI: 10.1159/000433527
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Clinical Presentation of Xeroderma Pigmentosum in a Patient Harboring a Novel Missense Mutation in the <b><i>XPC</i></b> Gene: The Importance of Clinical Suspicion

Abstract: Background: Xeroderma pigmentosum (XP) is a genodermatosis caused by abnormal DNA repair. XP complementation group C (XPC) is the most frequent type in Mediterranean countries. We describe a case with a novel mutation in the XPC gene. Case: A healthy Caucasian male patient was diagnosed with multiple primary melanomas. Digital follow-up and molecular studies were carried out. Results: During digital follow-up 8 more additional melanomas were diagnosed. Molecular studies did not identify mutations in CDKN2A, CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The majority of reported XPC mutations result in Premature Termination Codons (PTCs) [ 36 , 39 42 ]. There are few reports of missense type mutations in the XPC gene [ 41 , 43 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of reported XPC mutations result in Premature Termination Codons (PTCs) [ 36 , 39 42 ]. There are few reports of missense type mutations in the XPC gene [ 41 , 43 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, only five reports with six patients have been reported regarding the utility of dermoscopy for diagnosing skin lesions in XP patients. 1,[5][6][7][8] Here, we report a rare case of XP variant type (XPV) with dermoscopic findings of lentigo maligna. In addition, we conducted a literature review for relevant articles regarding the use of dermoscopy in XP.…”
Section: Lentigo Maligna In a Patient With Xeroderma Pigmentosum Varmentioning
confidence: 96%
“…To the Editor, Xeroderma pigmentosum (XP) is a rare autosomal recessive genetic disorder affecting the DNA repair system, which is vital to mend the damage caused by ultraviolet (UV) radiation. 1,2 XP patients usually develop multiple skin tumors including basal cell carcinoma (BCC), squamous cell carcinoma (SCC), malignant melanoma (MM), and angiosarcoma. 3,4 However, the diagnosis of these tumors is often difficult due to severe actinic damage caused by the UV radiation.…”
Section: Lentigo Maligna In a Patient With Xeroderma Pigmentosum Varmentioning
confidence: 99%
“…Functional testing of UV-induced DNA repair synthesis (UDS) in his skin fibroblasts was ∼40% of normal after a UVR dose of 10 Jm-2 suggesting that the XPC protein was partially functional, demonstrating the pathogenicity of the observed missense variants (Fassihi et al 2016). Additionally, Meneses et al (2015) also observed late-onset xeroderma pigmentosum in an individual heterozygous for a missense variant (p.Thr738Ala) and a frameshift variant (p.Leu763Cysfs * 4). These data suggest that hypomorphic alleles can lead to an atypical late-onset presentation of XP, group C.…”
Section: Variant Interpretationmentioning
confidence: 97%
“…Although c.1709T > G has not been descried in the literature or population databases, other missense variants in XPC have been reported in individuals with similar clinical features, including late-onset XP manifestations (Chavanne et al 2000;Bernardes de Jesus et al 2008;Meneses et al 2015;Fassihi et al 2016). Fassihi et al describe a patient with a homozygous missense variant (p.Tyr585Cys) in XPC who did not develop their first melanoma until age 28, and who displayed almost no pigmentary changes.…”
Section: Variant Interpretationmentioning
confidence: 99%